The Fluorescein Angiographic Signs of Aggressive Posterior Retinopathy of Prematurity - E. I. Saidasheva; S. V. Buynovskaya; F. V. Kovshov; Yu. V. Levadnev; O. Y. Shishkanova (Oftalʹmologiâ, 2019)
The purpose is to study the fluorescence angiographic signs of posterior aggressive retinopathy of prematurity. Patients and methods. A prospective study of 83 infants with aggressive posterior retinopathy of prematurity (APROP), who were on treatment in the neonatal center in 2012–2018 years. Gestational age was between 22 and 30 weeks. Depending on the diagnostic methods, patients were divided into two groups: 1 (main) — 51 (61.4 %) children who, in addition to standard ophthalmic examination methods, received 132 series of FA using a pediatric retinal camera RetCam3; 2 (control) — 32 (38.6 %) children without FA. After the procedure, the somatic state of the child was monitored for 24 hours for the registration of drug dye side effects. Results. Angiographic predictors of the disease and objective signs of APROP manifestation were presented in group 1 children a week earlier than in the group 2. This made laser treatment possible on 2.0 ± 0.5 weeks earlier in the group 1 (32.8 ± 1.2 weeks) compared to group 2 (34.8 ± 1.7 weeks) (p < 0.05) and to increase its efficiency by 8.2 % (86.3 and 78.1 % respectively). Conclusion. Comparative analysis of angiograms and color fundus images obtained with RetCam3 in the studied groups of children demonstrates the advantages and safety FA for the detection angiographic predictors of APROP, early objective signs of disease manifestation, it provides timely and effective laser treatment of complicated categories of very premature infants.